Pengaruh Pembelajaran Kooperatif terhadap Kecemasan Matematika - Risma Nurul Auliya (Universitas Indraprasta PGRI Jakarta, 2017)
The aim of this research is intended to examine the effect of cooperative learning model towards students’ mathematics anxiety. The research utilized a quasi experimental design. The population in this research was grade-8 students of a junior high school in South Jakarta. The sample comprised 32 students in cooperative group (as the experiment group) and 34 students in conventional group (as the control group). The instrument comprised Mathematics Anxiety Questionnaire (MAQ). The research problem was to examine the difference of mathematics anxiety between students in cooperative group and conventional one. The quantitative analysis used Mann-Whitney U test, while qualitative analysis used descriptive one. The result showed that students’ mathematics anxiety in cooperative group was lower than conventional one.